2011
DOI: 10.1038/nutd.2011.7
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of saturated versus unsaturated dietary fatty acids on weight gain and myocellular lipid profiles in mice

Abstract: Objective:In conditions of continuous high-fat (HF) intake, the degree of saturation of the fatty acids (FAs) in the diet might have a crucial role in the onset of obesity and its metabolic complications. In particular, the FA composition of the diet might influence the storage form of lipids inside skeletal muscle. The aim of the present study was to examine whether the FA composition of HF diets differentially affects weight gain and accumulation of myocellular triacylglycerol (TAG) and diacylglycerol (DAG).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 43 publications
(46 reference statements)
5
24
0
Order By: Relevance
“…On the other hand, it was found that the different test oils had resulted in fat deposition to different extents in the subcutaneous and visceral tissues as well as total fat:feed (Table 3). Hence, the present study shows that body mass gain and fat deposition do not necessarily occur in tandem, and this clarifies the previous studies ( 1 , 8 ) , which used body mass gain as the marker for obesity. We, therefore, focused on normalisation data (Table 3), namely fat:feed, in the present evaluation of diet-induced adipogenic oils.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…On the other hand, it was found that the different test oils had resulted in fat deposition to different extents in the subcutaneous and visceral tissues as well as total fat:feed (Table 3). Hence, the present study shows that body mass gain and fat deposition do not necessarily occur in tandem, and this clarifies the previous studies ( 1 , 8 ) , which used body mass gain as the marker for obesity. We, therefore, focused on normalisation data (Table 3), namely fat:feed, in the present evaluation of diet-induced adipogenic oils.…”
Section: Discussionsupporting
confidence: 89%
“…Generally, the intake of saturated fats has been perceived to exert deleterious effects on body fat deposition. Nonetheless, cocoa butter, a saturated fat, which has 63 g SFA/100 g total fatty acids, has been reported to prevent weight gain when compared with olive oil and safflower oil due to the presence of high amounts of palmitic and stearic acids ( 8 ) .…”
mentioning
confidence: 99%
“…The observation reported in previous literature ( 4 ) that COB is better at preventing fat accretion than palm oil has been successfully elucidated in the present study. Besides this, in our previous work ( 14 ) , we observed that dietary oil containing high amounts of linoleic and linolenic acids at sn -1, 3 positions, such as soyabean oil, led to significantly higher fat deposition than the diet enriched with palm olein.…”
Section: Discussionsupporting
confidence: 70%
“…Obesity is a cardiovascular risk factor that is also associated with a substantial increase in the risk of type 2 diabetes, hypertension and lipoprotein metabolism disorders. Concerted efforts have been made to establish the relationship between obesity and lipid intake; yet, most of the studies are merely based on the total SFA ( 1 4 ) , total unsaturated fatty acid ( 1 5 ) , MUFA ( 3 ) , n -6 PUFA ( 3 , 6 9 ) and n -3 PUFA ( 8 , 10 12 ) contents of edible oils. In general, a high-SFA-rich diet is perceived to be more obesogenic than diets with lower saturated contents ( 1 3 ) .…”
mentioning
confidence: 99%
“…For example, in rats, dietary fats from an animal source, such as lard, have a more pronounced effect on adiposity and insulin resistance than vegetable fats 142 . Even subtle modifications, such as changes in the ratio of unsaturated to saturated fatty acids 143 and the physical form of the diet (liquid versus solid) 144,145 , lead to different DIO outcomes. For example, the fat source used for the preparation of HFDs is the critical element that determines whether germ-free mice are resistant or susceptible to DIO [146][147][148] .…”
Section: Dio-sensitive Sprague Dawleymentioning
confidence: 99%